Suicide with Potassium Cyanide Bought on The Internet: A Case Report - Ata Öztürk, Hatice Kübra; Akça, Alper; Kurtuluş Dereli, Ayşe (The Bulletin of Legal Medicine, 2020)
Cyanide is one of the most toxic substances known. Although acute intoxication isn’t common, suicide with cyanide often results in death. In this study, it was present a 27-year-old man who suicide by buying potassium cyanide from the Internet. A cup with white contamination was found at the scene and an invoice and a credit card payment slip documenting that he had purchased 1 kg of potassium cyanide from a company selling chemical materials over the internet. In autopsy, nonspecific findings such as submucosal congestion and focal fresh bleeding areas and severe hyperemia in other tissues were found and the toxicological examination revealed that he died of oral cyanide poisoning. This study is presented in order to draw attention to the fact that cyanide, which is the most toxic substance known, can easily be bought over the internet and to emphasize that access to these substances should be strictly controlled.
Keywords: cyanide; poisoning; suicide; internet; autopsy